ANALYSIS OF FACTORS INFLUENCING SAVING BEHAVIOR AMONG GENERATION Y IN BATAM CITY - Sutini Sutini; Wisnu Yuwono (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The purpose of this study is to analyze the effect of the variables on the millennial generation in Batam City. This study covers three independent variables namely peer influence, parental socialization, and financial attitude towards the dependent variable namely saving behavior, with financial literacy as mediating variable. By using purposive sampling and a five-point Likert scale questionnaire, this study collected sample from 400 millennials in Batam City. The SmartPLS application version 3.2.9 is used to investigate the relationship between variables. The empirical results state that peer influence, parental socialization, financial attitude have a significant positive effect on financial literacy, subsequently financial literacy mediates a significant positive effect between peer influence, parental socialization, financial attitude towards saving behavior, and lastly financial literacy has a significant positive effect on saving behavior of the millennial generation in Batam City. All of these findings are very important because they will help the authorized institutions to develop policies for millennials on how to respond and manage money to save wisely.